Kualitas Pelayanan M-Paspor Di Kantor Imigrasi Kelas I TPI Jember - Helpiastuti, Selfi Budi; Syaifana, Irba; Rohman, Hermanto (Universitas Dr. Soetomo Surabaya, 2023)
This article aims to describe and analyze the service quality of the M-PASPOR application at the Class I Immigration Office TPI Jember. M-PASPOR was launched in an effort to improve the quality of passport application services, which were previously done manually. This application can be accessed anywhere and anytime by the public to apply for a new passport or change of passport. The service quality measurement method uses the Egovqual theory with four quality dimensions (efficiency, trust, reliability, and citizen support). This study uses a descriptive quantitative approach. Sampling in this study used an accidental sampling technique and obtained a total of 97 samples. The sample identification criteria are people who have used the M-PASPOR application. The data collection technique used in this study was the distribution of questionnaires. Validity and reliability testing were used in this study using SPSS 25. The analysis of the data used in the study is the GAP calculation by assessing the difference in perceptions and expectations of the community using the M-PASPOR application, followed by Importance Performance Analysis (IPA). Based on the results of the gap analysis, the service quality of the M-PASPOR application is in the not good category with a total score of -0.335. Based on the results of the IPA, there are several items that fall into categories that require improvement. These items are regarding form filling instructions, electronic media to access M-PASPOR, information in the M-PASPOR application, timeliness of service through M-PASPOR, speed of accessing applications, and username and password security in the M-PASPOR application.